Multiple Bone Metastases as the First Manifestation of Hepatocellular Carcinoma in Patient with Noncirrhotic Liver - Soo Ya Bae; Hyun Jung Kim; Hyun Ho Oh; Min Kwan Kwon; Jong Ho Lee; Moon Park; Byeong Seok Sohn (Case Reports in Oncological Medicine)
Hepatocellular carcinoma (HCC) generally occurs on the background of chronic liver disease. Chronic hepatitides B and C and alcoholic liver disease are well-known risk factors for HCC, and it is uncommon in noncirrhotic liver. Extrahepatic metastasis seldom occurs in patients with early stage intrahepatic HCC and isolated bone metastases as a first documented extrahepatic metastasis is unusual presentation. In this report, we present a rare case of small solitary HCC (<3 cm) in noncirrhotic liver, presenting isolated bone metastases as a sole manifestation in patient with no well-known risk factors. This case suggests that HCC should be considered as one of differential diagnoses in patient presenting with multiple bone metastases, even in the absence of liver cirrhosis.